Fast multiphase MR imaging of aqueductal CSF flow: 2. Study in patients with hydrocephalus. - Mascalchi, M; Ciraolo, L; Bucciolini, M; Inzitari, D; Arnetoli, G; Dal Pozzo, G (American Journal of Neuroradiology, 1990)
The signal intensity in the region corresponding to the cerebral aqueduct was evaluated in three patients with noncommunicating tension hydrocephalus (caused by aqueductal obstruction in two and type I Arnold-Chiari malformation in the other), seven patients with suspected normal-pressure hydrocephalus (three of whom subsequently underwent successful shunting), and 10 patients with ex vacuo (atrophic) hydrocephalus. A gradient-echo MR sequence, called fast multiphase imaging, was used. Serial images corresponding to different phases of the cardiac cycle were acquired. No flow-related enhancement was observed over the entire cardiac cycle in the patients with noncommunicating hydrocephalus. Patients with normal-pressure hydrocephalus showed a higher aqueductal CSF signal intensity, consistent with increased systolic flow rates, than patients with ex vacuo hydrocephalus. When comparing the above two groups of patients with a control group of healthy volunteers, significantly higher and lower values of the (mean) maximum aqueductal signal intensity were found in the normal-pressure hydrocephalus patients and the ex vacuo hydrocephalus patients, respectively. Fast multiphase MR evaluation of aqueductal CSF flow may help to differentiate patients with different types of hydrocephalus.